Personality and Risk for Alzheimer’s Disease in Adults 72 Years of Age and Older: A Six-Year Follow-Up - Duberstein, Paul R. (2011)
We conducted secondary analyses to determine the relationship between longstanding personality traits and risk for Alzheimer’s disease (AD) among 767 participants 72 years of age or older who were followed for more than 6 years. Personality was assessed with the NEO-FFI. We hypothesized that elevated Neuroticism, lower Openness, and lower Conscientiousness would be independently associated with risk of AD. Hypotheses were supported. The finding that AD risk is associated with elevated Neuroticism and lower Conscientiousness can be added to the accumulating literature documenting the pathogenic effects of these two traits. The link between lower Openness and AD risk is consistent with recent findings on cognitive activity and AD risk. Findings have implications for prevention research and for the conceptualization of the etiology of Alzheimer’s Disease.